Handbook on Labour Market Experiences of Community College Graduates - Manitoba Dept. of Labor and Manpower, Winnipeg; Manitoba Dept. of Labor and Manpower, Winnipeg ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Based on follow-up studies of the 1975, 1976, and 1977 Manitoba Community College graduates, this handbook outlines the employment experiences of graduates from 20 vocational programs in the health and personal services, business and administrative studies, applied arts, industrial and technological arts, and teacher education divisions. Programs offered at MCC within each vocational area are listed along with: (1) a program description from the college calendar; (2) a description of the duties of the jobs for which the program provides training; (3) the employment rate of students who graduated from the course; (4) the locations of employment; (5) starting salaries; (6) possible organizations where students can seek employment after training; and (7) the actual jobs attained by program graduates one year after graduation. Although the handbook is designed as an information source for identifying possible employment opportunities, the authors urge caution in its use since labor market conditions and employment situations will continue to change. (JP)
ERIC Note: Tables with small type may not reproduce well.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Allied Health Occupations Education; Business Education; College Graduates; Community Colleges; Employment Patterns; Employment Potential; Graduate Surveys; Salaries; Tables (Data); Teacher Education; Technical Education; Trade and Industrial Education; Two Year Colleges; Vocational Followup; Manitoba; Numerical/Quantitative Data; Reports, Research